A review of life cycle assessments of renewable energy systems - Ozoemena, Matthew; Hasan, Reaz; Cheung, Wai; Hackney, Philip (Cranfield University Press, 2013)
A review of life cycle assessments (LCAs) of wind energy published in the past few years are presented in this paper. The aim is to identify the differences of the developed methodologies, in particular, the factors such as methods used, energy performance and influence of uncertainty. Each of the factors is addressed to highlight the shortcomings and strengths of various approaches. Potential issues were identified regarding the way LCA is used for assessing environmental impact and energy performance of wind energy. It is found that the potential of incorporating the quantification of uncertainty in the manufacturing phase has not been studied elaborately. A framework methodology has been proposed in this paper to address this issue.
Keywords: Uncertainty; LCA; Manufacturing processes